2015
DOI: 10.11648/j.cb.20150301.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lycopene on Altered Kidney Antioxidant Enzymes Activity and Functions in Streptozotocin-Induced Diabetic Wistar Rats

Abstract: Abstract:The present study assessed the effects of lycopene on kidney antioxidant enzymes activities and functions in streptozotocin-induced diabetic Wistar rats.Diabetes was induced in animals by single intra-peritoneal injection of streptozotocin. Thereafter the animals were randomly assigned into the following groups: Group I and II (Normal control + olive oil and Diabetic control + olive oil)while Group III to VI were treated with (10, 20 and 40 mg/kg of lycopene and 2 mg/kg glibenclamide) respectively. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In our investigation, it was observed that rats administered with lycopene, CoQ10 and their combination showed reduction in elevated blood glucose level. These findings are harmonious with the previous literatures (Mahajan et al, 2020;Pansare et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our investigation, it was observed that rats administered with lycopene, CoQ10 and their combination showed reduction in elevated blood glucose level. These findings are harmonious with the previous literatures (Mahajan et al, 2020;Pansare et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…STZ administered rats showed elevated level of blood glucose than control group. Raised in blood glucose was reported in DM induced by STZ to study diabetes and its complications (Pansare et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the kidney slices obtained from the diabetic animals and stained with the hematoxylin and eosin showed glomerular expansion and tubular alveolar degeneration. A previous work [99] mentioned that the induction with streptozotocin caused damage to the kidney tissue of diabetic rats, and the untreated group showed severe glomerular necrosis with lymphocyte hyperplasia when compared with the normal. This result is similar to the work carried out by Trujillo et al [100], who reported that abnormal levels of serum urea usually signify decreased renal function, so plasma urea is a recognized marker of glomerular filtration rate (GFR) and in nephropathy.…”
Section: Discussionmentioning
confidence: 95%